Secondary towns in urban-rural linkages: role and adaptability of small urban entrepreneurs - (:unkn) unknown (My University, 2015)
In densely populated East Africa mountains, small and medium sized towns are said to play an important role in changing urban-rural linkages. Small entrepreneurs and enterprises (SMEs) are numerous and dynamic and are part of the active stakeholders in trade and services activities and businesses. However, their integration in relational systems is asymmetric: if they are key actors for inward flows (supplying rural zones from outside areas), they are challenged by other stakeholders (cooperatives, bigger enterprises and middlemen) for outward flows (collecting and distributing farm productions). The issue of by-passing effects for secondary towns in spatial and economic integration networks is important.
Keywords: African Research